MS GLOW FOR MEN: DIGITAL MARKETING STRATEGY ON MEN'S FACIAL CARE PRODUCTS - Susilo, Daniel; Putranto, Teguh Dwi; Navarro, Charles Julian Santos (Economic and Bussiness Faculty, Dr Soetomo University, 2021)
Technological developments over the last few years have led to a strategy transformation from conventional to online. This digital marketing strategy is carried out by many local and traditional companies because they do not believe it is more effective than traditional marketing activities, such as using brochures and catalogs. Various products have started to take advantage of digital marketing strategies, including MS Glow men's facial care products. The method used in this research is content analysis of Krippendorff on Instagram @ during the period January 1, 2021 to January 31, 2021. The conclusion of this research are more to do with promotions that highlight information about MS Glow For Men and the benefits of using MS Glow For Men.Keywords: MS Glow For Men, Digital Marketing Strategy; Men’s Facial Care, Instagram; Content Analysis.